CURRENT PROBLEMS OF MODERN PHARMACY IN THE CONTEXT OF MEDICINAL PLANT CULTIVATION - Safarova Zakiya Teshaevna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: the article describes the cultivation of medicinal plants, progress in the field of agronomy and biotechnology, and current problems of modern pharmacy in the context of medicinal plant cultivation.